The role of worldviews, radicalization risk factors, and personality in harassment of scientists - Vukašin Gligorić; Carlotta Reinhardt; Ella Nieuwenhuijzen; Josha Orobio de Castro; Allard R. Feddes; Gerben A. van Kleef; Bastiaan T. Rutjens (Scientific Reports)
Abstract Anti-science movements brought more than public distrust in science. Perhaps even more worryingly, these movements are also associated with instances of harassment of—and violence against—scientists. However, virtually nothing is known about individuals likely to harass or harm scientists. Across two pre-registered studies (total N = 749), we investigated the role of worldviews (e.g., political ideology, conspiracy mentality, science cynicism), radicalization risk factors (relative deprivation and threat), and personality traits and how these relate to harassment of scientists (both attitudes and behavior). We found that science cynicism–the perception that scientists are incompetent and corrupt–drives approval of scientists’ harassment (attitudes), as well as harmful behavior (e.g., refusing to donate money, not signing a petition). Additionally, perceiving scientists as threatening, as well as dark personality traits (psychopathy and narcissism), contributed to approving scientists’ harassment. Overall, the present research takes a first step in identifying predictors of the willingness to harm scientists.